Estimating some parameters of shrimp fishery in Bangladesh - Ray, Ajit Kumar; Khan, MD. Shamim Uddin (Indian Journal of Fisheries, 2011)
The paper attempts to estimate annual expected shrimp stock of Bangladesh by applying the method suggested by Pauly for demersal stock in tropical zone subject to specific characters of marine area and trawler. Estimation ofcatchability coefficient q has been made from the published BOBP/DOF data.For testing reliability, q is used to obtain predicted harvest levels (h/) and compared with the actual harvest levels (h). The intrinsic growth rate (r) is also estimated by Verhulst growth equation.